Time lapse camera pictures at Samoylov, LTO, 2002-2017. - Boike, Julia; Nitzbon, Jan; Anders, Katharina; Grigoriev, Mikhail N; Bolshiyanov, Dimitry Yu; Langer, Moritz; Lange, Stephan; Bornemann, Niko; Morgenstern, Anne; Schreiber, Peter; Wille, Christian; Chadburn, Sarah; et al. (PANGAEA, 2018)
Most of the world's permafrost is located in the Arctic, where its frozen organic carbon con-tent makes it a potentially important influence on the global climate system. The Arctic climate appears to be changing more rapidly than the lower latitudes, but observational data density in the region is low. Permafrost thaw and carbon release into the atmosphere is a positive feed-back mechanism that has the potential for climate warming. It is therefore particularly im-portant to understand the links between the energy balance, which can vary rapidly over hour-ly to annual time scales, and permafrost condition, which changes slowly on decadal to cen-tennial timescales. This requires long-term observational data such as that available from the Samoylov research site in northern Siberia, where meteorological parameters, energy balance, and subsurface observations have been recorded since 1998. This paper presents the temporal data set produced between 2002 and 2017, explaining the instrumentation, calibration, pro-cessing and data quality control. Additional data include a high-resolution digital terrain mod-el (DTM) obtained from terrestrial LiDAR laser scanning. Since the data provide observations of temporally variable parameters that influence energy fluxes between permafrost, active lay-er soils, and the atmosphere (such as snow depth and soil moisture content), they are suitable for calibrating and quantifying the dynamics of permafrost as a component in earth system models. The data also include soil properties beneath different microtopographic features (a polygon center, a rim, a slope, and a trough), yielding much-needed information on landscape heterogeneity for use in land surface modeling. For the record from 1998 to 2017, the average mean annual air temperature was -12.3°C, with mean monthly temperature of the warmest month (July) recorded as 9.5°C and for the coldest month (February) -32.7°C. The average annual rainfall was 169mm. The depth of zero annual amplitude niveau is at 20.8m, and has warmed from -9.1°C in 2006 to -7.7°C in 2017.
Measurements in soil and air at Samoylov Station (2002-2018)